Peningkatan Kepuasan Pelanggan dengan Menggunakan Metode Pendekatan Service Performance dan Importance Performance Analysis (IPA) di Perumda Delta Tirta Sidoarjo - Anastasya, Rafidah Amelia; Sumiati, Sumiati (Universitas Batanghari Jambi, 2026)
The purpose of this study was to determine the level of customer satisfaction with the quality of service at Perumda Delta Tirta Sidoarjo. The primary data obtained from this study were the results of distributing questionnaires to 100 respondents who are active customers of Perumda Delta Tirta Sidoarjo. The questionnaires distributed to respondents were calculated using a Likert scale weighting. The results of the study indicate that there is a high level of customer satisfaction with the service performance at Perumda Delta Tirta Sidoarjo, with several things that need to be improved, especially in the service provided by Perumda Delta Tirta Sidoarjo.